Deferoxamine inhibits iron-uptake stimulated osteoclast differentiation by suppressing electron transport chain and MAPKs signaling. (1st October 2019) - Zhang, Jian; Hu, Wentao; Ding, Chong; Yao, Gang; Zhao, Hai; Wu, Shuguang
Highlights: Deferoxamine inhibits iron-uptake stimulated osteoclast differentiation. Deferoxamine results in a marked decrease in cellular iron. Deferoxamine decreases activities of all the mitochondria complexes. Deferoxamine increases ROS production in mitochondria and inhibits MAPKs activation. Deferoxamine pretreatment inhibits MAPKs activation even in the presence of ROS. Abstract: Iron overload causes osteoporosis by enhancing osteoclastic bone resorption. During differentiation, osteoclasts demand high energy and contain abundant mitochondria. In mitochondria, iron is used for the synthesis of Fe-S clusters to support mitochondria biogenesis and electron transport chain. Moreover, mitochondrial reactive oxygen species (ROS) play an important role in osteoclastogenesis. Activation of MAPKs (ERK1/2, JNK, and p38) by ROS is essential and contribute to osteoclast differentiation. How iron chelation impairs electron transport chain and ROS dependent MAPKs activation during osteoclast differentiation is unknown. This study aimed to determine the direct effects of iron chelation on osteoclast differentiation, electron transport chain and MAPKs activation. In the present study, we found that when iron chelator, deferoxamine (DFO), was added, a dose-dependent inhibition of osteoclast differentiation and bone resorption was observed. Supplementation of transferrin-bound iron recovered osteoclastogenesis. Iron chelation resulted in a marked decrease in ferritin level, and increased expression of transferrin receptor 1 and ferroportin. As an iron chelator, DFO negatively affected mitochondrial function through decreasing activities of all the complexes. Expressions of mitochondrial subunits encoded both by mitochondrial and nuclear DNA were decreased. DFO augmented production of mitochondrial ROS, but inhibited the phosphorylation of ERK1/2, JNK, and p38, even in the presence of hydrogen peroxide. These results suggest that iron chelation directly inhibits iron-uptake stimulated osteoclast differentiation and suppresses electron transport chain. Iron chelation negatively regulates MAPKs activation, and this negative regulation is independent on ROS stimulation.